(untitled)
Water balance analysis of the humid tropical Kerala, India shows that evaporative demand exceeds rainfall for five to seven consecutive months in a year. For scheduling of irrigation at 20, 30, 40, 50, 60 and 70 per cent of the available water capacity (A WC) in laterites, 1he cumulative evaporation values for coconut (Cocos nucifera Linn.), arecanut (Areca catechu